Fitness costs and the rapid spread of kelch13-C580Y substitutions conferring artemisinin resistance - Nair, S; Li, X; Arya, G; McDew-white, M; Ferrari, M; Nosten, F; Anderson, T (American Society for Microbiology, 2018)
Fitness costs are key determinants of whether drug resistance alleles establish and how fast they spread within populations. More than 125 different kelch13 alleles, each containing a different amino acid substitution, have arisen in SE Asian malaria parasite (Plasmodium falciparum) populations under artemisinin selection over the past 15 years in a dramatic example of a soft selective event. However, just one of these alleles (C580Y) is now outcompeting other alleles in multiple different countries and is spreading towards fixation. Here we examine the fitness consequences of C580Y, relative to another less successful kelch13 mutation (R561H), to try to explain the distinctive dynamics of C580Y. We hypothesized that C580Y will show lower fitness costs relative to other kelch13 substitutions in the absence of artemisinin treatment. We used CRISPR/Cas9 methods to introduce single mutations (C580Y or R561H), or synonymous control edits into a wildtype parasite isolated on the Thailand-Myanmar border, conducted replicated head-to-head competition assays, and determined the outcome of competition using deep sequencing of kelch13 amplicons. Contrary to our predictions, these experiments reveal that C580Y carries higher fitness costs (s=0.15 ± 0.008 [1 s.e.]) than R561H (s=0.084 ± 0.005). Furthermore, R561H outcompetes C580Y in direct competition (s=0.065 ± 0.004). We conclude that fitness costs of C580Y in isolation are unlikely to explain the rapid spread of this substitution.